The Problem of Real Estates in Algeria during the Second Half of the Nineteenth Century (1850-1900) - ben moussa, Hammadi (The Algerian Historical Journal, 2026)
As early as 1834, the French colonial administration had made it very clear that Algerian territory is not treated not only as conquered territory but as part and parcel of France’s own territorial mainland. Hence, the famous/infamous law of Senatus-Consult of 1863 with which France had to profit from its war of conquest by appropriating huge real estates properties. The present article addresses several updates of the same law during the third republic both in 1873 and 1887. The article traces also the native elites’ responses to the massive dispossession as this law become actionable